Two new bithecal earthworms of the genus Amynthas (Oligochaeta: Megascolecidae) from Laos - Hong, Yong (Zootaxa, 2008)
Earthworm specimens collected from Nam Phouin NBCA, Laos were found to be two new species of megascolecid earthworms: Amynthas namphouinensis sp. nov. and Amynthas chandyi sp. nov. They belong to the zebrus species group with a pair of spermathecal pores in 7/8. A. namphouinensis has male pores on small round porophores in XVIII, genital papillae always paired equatorial in XVII, presetal, widely paired in XIX, and mid-ventral in 17/18. A. chandyi has male pores on circular porophores in XVIII, and genital papillae paired in 18/19 posterior to the porophores, postsetal in XVIXIX, and presetal in XVIII, XX.